"Portalitis" (Journal of Parents and Teachers, 2014)
The Internet has grown very quickly and so have many portals; as a consequence, it is essential to take into account various elements such as: its design, the search engine it has, the services it offers, the content and the speed of the search.In the following article, a small comparison is made with some of the best known portals such as: Yahoo, MSN, Lycos, etc.
Keywords: comparative; study; portals